Information practices of urban newcomers: An analysis of habits and wandering. (16th July 2014) - Lingel, Jessa
<x xml:space="preserve">Abstract</x> This paper reviews information practices used by transnational migrants to become familiar with new urban surroundings. Drawing on interviews with 26 participants, all of whom had moved to New York City in the past 2 years, I analyze the interrelatedness of people, city space, and technology. By rooting my analysis in the experiences of transnational newcomers to New York, my investigation is directed both at library and information science (LIS) scholarship in transnational experience and urban informatics as an area of study. The findings section first addresses participants' practices for becoming familiar with their surroundings as embedded in everyday routines using Bergson's (1911) construct of habits as a means of organizing stimulus. I then develop an analysis of wandering, which emerged as an information practice used by participants to become familiar with their neighborhoods. Building on these themes, I suggest implications for human information behavior theory, arguing that LIS scholars should articulate more clearly and across a wider range of disciplines the concepts of mobile and ubiquitous technologies.